HUBUNGAN TINGKAT KEBUGARAN JASMANI DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATA PELAJARAN PENJAS PADA KURIKULUM 2013 - Suci Nanda Sari (Jurusan Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2020)
Abstract The problem in this research is the not optimal student learning outcomes in Physical Education subjects. The research objective is to see the relationship between the level of physical fitness and learning motivation with learning outcomes in Physical Education subjects in the 2013 curriculum. This research is correlational. The population in this study were junior high school students in the city of Padang. The sample collection technique used random purposive sampling, amounting to 32 students. The test instruments were the TKJI test, motivation questionnaire analysis, and physical education learning outcomes scores. The analysis technique uses correlation with SPSS version 16. The results of the study at the significant level α = 0.05 are 1) There is a significant relationship between the level of physical fitness and the learning outcomes of Physical Education subjects in the 2013 curriculum. 2) There is a significant relationship between learning motivation and learning outcomes of Physical Education subjects in the 2013 curriculum. 3) There is a significant relationship between the level of physical fitness and learning motivation with learning outcomes in Physical Education subjects in the 2013 curriculum. Keywords: Physical Fitness Level, Learning Motivation, Learning Outcomes